ANALISIS LOYALITAS KONSUMEN MUSLIM TERHADAP STARBUCKS COFFEE PASCA DUKUNGAN STARBUCKS TERHADAP LGBT - Muhammad Reza; Saparuddin Siregar; Marliyah Marliyah (Universitas Islam Negeri Sumatera Utara, 2020)
Starbucks as well as other companies requires loyalty from its customers to increase the quantity of sales. However, it seems that Starbucks does not care about the loyalty of Muslim customers. This is evident from the Starbucks support campaign for LGBT which is clearly the opposite of Islamic teachings. Because, if Muslims are loyal to Starbucks who are known to support LGBT, it means that Muslims play a role in supporting LGBT. The purpose of this study is to find out Muslim consumer loyalty to Starbucks after Starbucks supported LGBT and also to find out Muslim consumers' responses to Starbucks for providing support Starbucks Coffee in the LGBT community. This study was conducted using qualitative methods. In this study the authors found that Starbucks support for LGBT is an act that violates business ethics in the scope of social responsibility. Moreover LGBT is a for acts that are forbidden in Islam. So Starbucks support for LGBT actions received a positive response from Muslim consumers. From informants who were questioned there was not one informant who agreed with Starbucks Coffee's support for LGBT. 3 of the 5 informants lost their loyalty to Starbucks and reluctant to go back to Starbucks.